LIBERAL IDEAS AND STATE REGULATION ON THE WAY OF SOCIO-ECONOMIC DEVELOPMENT OF UKRAINE - S. M. Prylypko; T. Kasiliunas (Фінансово-кредитна діяльність: проблеми теорії та практики)
The main purpose of the article is to substantiate the socio-economic development of Ukraine on the basis of partnerships between market participants, where the state acts as the main regulator of socio-economic processes. The article emphasizes that the current liberal ideas prevailing in Ukraine regarding the further development of the state’s economy do not meet the existing prerequisites for the development of market relations. It is emphasized that state ideology should consolidate society around integrated ideas of development in social, economic and technological directions. The opinion is expressed that in order to modernize the Ukrainian economy, it is necessary to implement the state regulation of the economy, which should form the skills of doing business on the terms of partnership, which is realized in turn, through the remuneration of workers, and it should increase the general level of welfare of the country’s population. It is justifies that liberal ideas in the economy should be limited to the time of formation of social and cultural preconditions for the development of free trade and the capital movement. It is concluded that state regulation of the economy is the optimal way of socio-economic development of Ukraine. In the absence of a proper resource base for Ukraine’s socio-economic development, the country’s economic policy should strengthen state regulation of economic relations. The economy of the country should be aimed at raising the well-being of the population and forming a culture of doing business, rather than enriching the owners of means of production at any cost. Socialization of the economy should occur not by increasing social payments, but by raising wages through the distribution of corporate profits. Increasing opportunities for people to access social goods is the key to creating a new quality of intellectual capital in the country. In order to develop the country’s economy, it is first of all necessary to form social and cultural preconditions. Liberal ideas of free movement of capital, in particular towards the outflow from Ukraine, can only be implemented after stabilization of the country’s economy and its progressive growth. State regulation in the economy is not only the control of the movement of financial flows, but also the control of the movement of labor and the prevention and cessation of loss of intellectual potential of Ukraine. The state as an economic entity should be impersonal, and any actions of officials should be the actions of the state, not of a specific power or political force. While building the economy of a country with rigid government regulation, economic agents must acquire the skills to fulfil contractual terms, and government entities are no exception. Only after we learn how to negotiate and fulfil contractual obligations will we be able to speak about the mitigation of government intervention in the economy. State regulation of the economy in Ukraine today is the only way to stop chaotic development.